2017
DOI: 10.5455/ajvs.273717
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of TLR4 Gene and Its Association With Genetic Resistance to Salmonella Enteritidis Infection in Fayoumi Breed and Hy-line Strain in Egypt

Abstract: Key words:Toll-like receptor, polymorphism, genetic resistance, salmonella enteritidis, chickenThe aim of this study is to investigate the polymorphism in exon1 and 2 of TLR4 gene and its possible association with resistance to salmonella infection in the Fayoumi breed and Hyline strain of chickens and its possible association with immune response of birds under study. Two experiments were done, in which the chicks were infected intraesophageal with two different doses of S. enteritidis LD 50 (10 8 cfu) in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…B allele was more frequent than A allele in the three breeds. DNA fragments reported in the current study were similar to those obtained by KHATAB et al, (2017); however with different gene and genotypic frequencies. The authors reported the association between TLR4 gene and genetic resistance/susceptibility to Salmonella enteritidis in Fayoumi and Hy-line strain in Egypt.…”
Section: Tlr4 Gene Expression Patternsupporting
confidence: 80%
See 2 more Smart Citations
“…B allele was more frequent than A allele in the three breeds. DNA fragments reported in the current study were similar to those obtained by KHATAB et al, (2017); however with different gene and genotypic frequencies. The authors reported the association between TLR4 gene and genetic resistance/susceptibility to Salmonella enteritidis in Fayoumi and Hy-line strain in Egypt.…”
Section: Tlr4 Gene Expression Patternsupporting
confidence: 80%
“…LEVEQUE et al, (2003) indicated that, there was a link between TLR4 gene variation and susceptibility to Salmonella enterica serovar typhimurium infection in chickens. Analysis of chicken TLR4 genes in a Salmonella enteritidis resource population of chickens has been investigated (MALEK et al, 2004;TOHIDI et al, 2012;KHATAB et al, 2017). Similarly, LIU et al, 2011 studied relatedness between genetic polymorphism at exon2 of TLR4 gene and resistant traits in chicken.…”
Section: Tlr4 Gene Expression Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular marker characterisation along with functional genomic methods provide opportunities for enhancing genetic improvement programs in chickens (Gao et al 2007). Single nucleotide polymorphisms (SNP) have been used in association studies, but PCR-RFLP, as a rapid, low cost technique, has been used to assess SNP in candidate genes responsible for a variety of physiological functions in chickens (Hasenstein et al 2006;Hasenstein and Lamont 2007;Khatab et al 2017;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, several studies have reported associations between immune genes and growth, immune response, bacterial burden and antibody titres against Salmonella spp. in chickens (Kramer et al 2003;Khatab et al 2017;Saleh 2019;Thinh et al 2019). Research on potential candidate genes and their use in selection programmes for improving immunity, bacterial load and antibody titres response and for increasing genetic resistance against Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%